Bioactive anti-oxidative polycaprolactone/gelatin electrospun nanofibers containing selenium nanoparticles/vitamin E for wound dressing applications. (August 2021) - Doostmohammadi, Mohsen; Forootanfar, Hamid; Shakibaie, Mojtaba; Torkzadeh-Mahani, Masoud; Rahimi, Hamid-Reza; Jafari, Elham; Ameri, Alieh; Amirheidari, Bagher
In this study, polycaprolactone/gelatin (PCL/GEL) electrospun nanofibers containing biogenic selenium nanoparticles (Se NPs) and Se NPs/vitamin E (VE) with average diameters of 397.8 nm and 279.5 nm, respectively (as determined by SEM inspection) were prepared and their effect on wound healing was evaluated using in-vivo studies. The energy dispersive X-ray (EDX) mapping, TEM micrograph, and FTIR spectra of the prepared nanofibers strongly demonstrated well entrapment of Se NPs and VE into scaffolds. An amount of 57% Se NPs and 43% VE were gradually released from PCL/GEL/Se NPs/VE scaffold after 4 days immersion in PBS solution (pH 7.4). The both PCL/GEL/Se NPs and PCL/GEL/Se NPs/VE scaffolds supported 3T3 cell proliferation and attachment as confirmed by MTT assay and SEM imaging. Complete re-epithelialization, low level of edema and inflammatory cells in coordination with high level of oriented collagens demonstrated the wound healing activity of PCL/GEL/Se NPs/VE. Besides, significant antioxidant efficacy of PCL/GEL/Se NPs and PCL/GEL/Se NPs/VE scaffolds was demonstrated according to GSH and MDA assays. To sum up, the prepared PCL/GEL/Se NPs/VE scaffold in the present study represented suitable healing effect on animal model which candidate it for further studies.